Behavioural assessment unit improves outcomes for patients with complex psychosocial needs. (8th December 2017) - Braitberg, George; Gerdtz, Marie; Harding, Susan; Pincus, Steven; Thompson, Michelle; Knott, Jonathan
Abstract: Objective: We aimed to assess the impact of a new model of care for patients presenting to the ED with acute behavioural disturbance. Methods: This pre‐/post‐intervention study involved creating a dedicated, highly resourced six bed unit, the behavioural assessment unit (BAU). Co‐located with the ED at the Royal Melbourne Hospital, the unit was designed to fast‐track the admission of patients affected by intoxication, mental illness or psychosocial crisis and provide front‐loaded interventions. Results: In 12 months from 1 April 2016, 2379 patients were admitted to the BAU. They were compared with a similar cohort of 3047 patients from the entire 2015 ED population. The BAU resulted in a decreased wait to be seen (40 min [interquartile range (IQR): 17–86] vs 68 min [IQR: 24–130], P < 0.001), a decreased wait for a mental health review (117 min [IQR: 49–224] vs 139 min [IQR: 57–262], P  = 0.001) and a decreased ED length of stay (180 min [IQR: 101–237] vs 328 min [IQR: 227–534], P < 0.001). Patients admitted to the BAU were less likely to have a security code (349 (14.7%) vs 538 (17.7%), P  = 0.003) and less likely to have mechanical restraint (156 episodes (6.6%) vs 275 (9.0%), P  < 0.001) or therapeutic sedation (156 episodes (6.6%) vs 250 (8.2%), P  < 0.001). Conclusion: A unit specifically designed to improve the care of patients requiring prolonged ED care due to mental illness and/or intoxication reduces the time spent in the ED and the use of some restrictive interventions. We recommend this model of care to EDs that care for this complex and challenging group of patients.